2017
DOI: 10.1111/dar.12550
|View full text |Cite
|
Sign up to set email alerts
|

Are differences in population prevalence of alcohol's harm to others related to survey administration mode?

Abstract: A survey mode based on interviews seems to facilitate reports of harm from strangers' drinking. This does not apply to reports of harm from known people's drinking. Therefore, the comparability of estimates of alcohol's harm to others between survey modes depends on the type of harm being studied. [Sundin E, Landberg J, Galanti MR, Room R, Ramstedt M. Are differences in population prevalence of alcohol's harmto others related to survey administration mode?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Another possible limitation that we cannot rule out that the different modes of administration may have affected response patterns. However, a recent Swedish study found no association between mode of administration and harm from known people's drinking 28 . We also recognise the limitations of cross-sectional data with regard to inferring causality.…”
Section: )mentioning
confidence: 92%
“…Another possible limitation that we cannot rule out that the different modes of administration may have affected response patterns. However, a recent Swedish study found no association between mode of administration and harm from known people's drinking 28 . We also recognise the limitations of cross-sectional data with regard to inferring causality.…”
Section: )mentioning
confidence: 92%
“…face-toface interviews, telephone interviews, self-administrated postal and Web questionnaires). Previous studies suggest that the level of self-reported harm from others' drinking may be higher in surveys using telephone interviews than in studies using self-administrated postal or Web questionnaires (Johnson, 2014;Sundin et al, 2018). Response rates also varied between surveys (Moskalewicz et al, 2016).…”
Section: Methodological Considerationsmentioning
confidence: 99%